Santo Antão: The Jesuit College in Lisbon and its History - Giurgevich, Luana; Leitão, Henrique; Salomoni, David (Early Modern History and Modern History E-Books Online, Collection 2025, 2025)
"The volume delves into the multifaceted history of Lisbon's Jesuit College of Santo Antão, tracing its evolution from its establishment to the eventual suppression of the Society of Jesus. This scholarly work examines an array of themes, including the college's innovative pedagogical practices, its architectural developments, and its significant contributions to the preservation of a rich literary heritage. Moreover, the volume situates the institution within broader social and scientific context"-- Provided by publisher